(3GdGbJUGO aj GdGYJbGOs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s
(3ChdgG (B:s
(3hHYO agPG jfHZi Cf Jage GdOdjd hGdeOdhd hhLg GdOdGdI hMbjbI GdfXQ hOY Yfc eG ShQJ Hg ChQGb cKjQI ef JWhjdGJ s
(3BNQgG (B:s
(3jfHZi Cf jMce HcaQg dCfg ecPH jMJQR Yf GdJUQjM hGddg CYde HGdUhGH Je GdcJGH HMeO Gddg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B135s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJhMjO hGdedd hGdfMds